An Overview of Credit Report/Credit Score Models and a Proposal for Vietnam - Le, Thinh (VNU Journal of Science: Policy and Management Studies, 2017)
Having a national credit database system would help financial institutions (FIs) reduce credit risk and reduce non-recovered bad debts. The government will feel at ease when FIs and the people are protected from bad debts in a sustainably developing and transparent market. On the other hand, borrowers will also receive benefit. Those who have good credit history will be provided with a more favorable interest rate and less requirements, or even without collateral.  In 2014 the Vietnam National Assembly passed the Citizen Identity Law, which requires the government to issue a unique lifetime personal identification number for each citizen (starting 2016). This will play a crucial role in building a national credit database system. In this article we will give an overview of credit report and credit score models, mainly in the United States. Based on that, we draft a detailed proposal for a national credit database system which can be implemented in Vietnam.